An ELT textbook evaluation: A two-phase criterion - Negin Samoudi; Mohammad Mohammadi (Universitas Sarjanawiyata Tamansiswa, 2021)
It is by now well established that materials may have an impact beyond simply learning a language they present. Thus, we need to survey thoroughly the materials to find out the influence they might have on learners' progress and attitude. Hence, in this study attempts have been made to investigate the cons and pros of a textbook (Summit 2B) which is currently being widely used in Iranian EFL classes. The textbook has been evaluated based on a model provided by McDonough and Shaw (1993) on the basis of two stages: an external evaluation that offered a brief overview of the textbook from the outside and a closer and more detailed internal evaluation. Efforts have been made to critically evaluate the textbook in terms of the layout, design, content, language type, different activities, tasks, as well as the skills emphasized in the book. The findings showed that albeit there appears to be some shortcomings, this book (Summit 2B) seems to be more efficient to meet the requirements of the Iranian EFL learners as compared with the older textbooks which have hitherto been used at different language classes. Accordingly, investigating and evaluating the book proved to be very lucrative and valuable in terms of pedagogy as well as the efficient attributes that suits the context of the present study.Â Finally, the implications as regards the efficiency of this particular course-book as the consequence of evaluating it have been put forward and the strengths and weaknesses related to it have been argued.